Electromechanical drive management energy - N. I. Smolentsev; L. M. Chetoshnikovа; A. N. Ignatov (Известия высших учебных заведений: Проблемы энергетики)
The development of an intelligent energy storage management system is an up-to-date scientific and technical challenge. This system should ensure maximum efficiency of energy storage in power networks for various purposes. The article discusses the use of energy storage in distribution networks of an industrial enterprise and substantiation of the vector control method of the inverted synchronous motor of the energy storage SPENE-1, shows a block diagram of the vector system for controlling the energy accumulator motor and the results of its simulation in MatLab.